A Conceptual Framework for Understanding the Cultural and Contextual Factors on Autism Across the Globe - Leeuw, Anne; Happé, Francesca; Hoekstra, Rosa A. (Autism research, 2020)
Autism research is heavily skewed toward western high‐income countries. Culturally appropriate screening and diagnostic instruments for autism are lacking in most low‐ and middle‐income settings where the majority of the global autism population lives. To date, a clear overview of the possible cultural and contextual factors that may affect the process of identifying and diagnosing individuals with autism spectrum disorders (ASD) is missing. This study aims to outline these factors by proposing a conceptual framework. A multidisciplinary review approach was applied to inform the development of the conceptual framework, combining a systematic review of the relevant autism research literature with a wider literature search spanning key texts in global mental health, cultural psychiatry, cross‐cultural psychology, and intellectual disability research. The resulting conceptual framework considers the identification, help‐seeking, and diagnostic process at four interrelated levels: (a) the expression; (b) recognition; (c) interpretation; and (d) reporting of autism symptoms, and describes the cultural and contextual factors associated with each of these levels, including cultural norms of typical and atypical behavior, culture‐specific approaches to parenting, mental health literacy, cultural beliefs, attitudes and stigma, as well as the affordability, availability, accessibility, and acceptability of services. This framework, mapping out the cultural and contextual factors that can affect the identification, help‐seeking, and diagnosis of ASD may function as a springboard for the development of culturally appropriate autism screening and diagnostic instruments, and inform future cross‐cultural autism research directions. The framework also has relevance for clinicians and policy makers aiming to improve support for underserved autism populations worldwide. Autism Res 2020, 13: 1029‐1050. © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary The vast majority of autism research is conducted in western high‐income settings. We therefore know relatively little of how culture and context can affect the identification, help‐seeking, and diagnosis of autism across the globe. This study synthesizes what is known from the autism research literature and a broader literature and maps out how culture and context may affect (a) the expression, (b) recognition, (c) interpretation, and (d) reporting of autism symptoms.